Characterizing CH4, CO2 and N2O emission from barn feeding Tibetan sheep in Tibetan alpine pastoral area in cold season. (May 2017) - Xu, Tianwei; Zhao, Na; Hu, Linyong; Xu, Shixiao; Liu, Hongjin; Ma, Li; Zhao, Xinquan
Abstract: Herein, methane (CH4 ), carbon dioxide (CO2 ) and nitrous oxide (N2 O) emission from different aged barn feeding Tibetan sheep were characterized using a respiration chamber in combination with gas chromatograph method in cold season of 2013. This work was based on measuring the increase of gas concentration inside respiration chamber by the means of gas chromatograph. Results indicated that diurnal CH4 emission patterns for barn feeding Tibetan sheep were driven by feeding schedule, diurnal CO2 emission patterns were relatively stable with two slight emission peaks, diurnal N2 O emission patterns were driven by the variation of temperature inside chamber. Diurnal CH4 emission rates were 17.65, 19.49 and 21.06 g sheep −1 d −1 for yearling, two-year and three-year barn feeding Tibetan sheep, account for 6.15%, 5.76% and 5.45% of their daily gross energy intakes, respectively. Diurnal CO2 emission rates were 526.88, 588.43 and 640.66 g sheep −1 d −1 for yearling, two-year and three-year barn feeding Tibetan sheep, respectively. Diurnal N2 O emission rates were 1.64, 1.25 and 1.05 mg sheep −1 d −1 for yearling, two-year and three-year barn feeding Tibetan sheep, respectively. Three-year barn feeding Tibetan sheep released more CO2 -eq on per unit BW and BW 0.75 gain basis. Highlights: Diurnal CH4, CO2 and N2 O emission rates for barn feeding Tibetan sheep were provided. CH4 conversion factors for different aged barn feeding Tibetan sheep were given. Diurnal CH4 emission patterns were driven by feeding schedule. Diurnal N2 O emission patterns were driven by diurnal variation of temperature. Elder barn feeding Tibetan sheep release more CO2 -eq on per kg BW and BW 0.75 gain basis.